(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2026)
This article examines the role of Eurocentric thought in shaping colonial representations of Malay sociopolitical culture in Perak during the formative period of British imperialism, particularly following the Pangkor Treaty of 1874. It argues that colonial discourse was structured by Eurocentric epistemologies that reconfigured indigenous images to legitimise imperial ideology. Adopting a qualitative method, the study analyses personal writings and official reports produced by British administrators who directly engaged with Perak in the late 19th-century. Figures such as Harry Ord, Andrew Clarke, John F. McNair, Frank Swettenham, William G. Maxwell and Hugh Clifford generated narratives that portrayed Malay society through colonial lenses. A close reading reveals how administrators strategically emphasised perceived backwardness, inefficiency and corruption in Malay political culture as rhetorical devices to rationalise imperial expansion. This construction advanced Britain’s dual claim: the extraction of local resources alongside a civilising mission that promised order, progress and humanitarian values. By renarrating local practices, inventing myths of sociopolitical deficiency and embedding Eurocentric frameworks, British officials manufactured a moral justification for exploitative governance. The study contributes to postcolonial historiography by highlighting how discourse, power and knowledge intersected in consolidating imperial control in Perak.